Histological analysis of the periapical tissues of dog deciduous teeth after root canal filling with diferent materials - Murata, Sueli Satomi [UNESP]; Holland, Roberto [UNESP]; Souza, Valdir de [UNESP]; Dezan Junior, Eloi [UNESP]; Grossi, Juliana Aguiar De; Percinoto, Célio [UNESP] (Faculdade De Odontologia De Bauru - USP, 2005)
The problem of finding an ideal material for filling root canals of deciduous teeth has not been solved yet. This fact led to the development of an experiment to histologically analyze the periapical tissue reaction to 3 root canal filling materials. Eighty root canals of dog deciduous anterior teeth from 6 animals, 60 days old, were used in this study. After biomechanical preparation, the root canals were filled with the following materials: slowly resorbable Maisto paste, Sealer 26 with iodoform, L&C paste (calcium hydroxide with olive oil) and as a control group, canals that were prepared but not filled. At thirty days after the treatment the animals were killed and the teeth prepared for histological analysis. The materials were ranked statistically from the best to the worst as follows: a - Maisto paste, b - Sealer 26 with iodoform, c - control group, d - L&C paste. There was significant difference (p = 0.01) only when the results of the other groups were compared with the L&C paste group. It was also observed that L&C paste was not biologically compatible and that the other materials were biocompatible but their resorption was not at the same rate as that of the deciduous teeth roots.

O objetivo de encontrar um material ideal para obturar canais radiculares de dentes decíduos ainda não foi alcançado. Esse fato estimulou a realização de uma experimentação para analisar histologicamente a reação dos tecidos periapicais a 3 materiais obturadores de canal. Assim, oitenta canais radiculares de dentes decíduos anteriores de 6 cães, com 60 dias de idade, fora empregados neste estudo. Após o preparo biomecânico, os canais radiculares foram obturados com os seguintes materiais: pasta lentamente reabsorvível de Maisto, Sealer 26 com iodofórmio, pasta L&C (hidróxido de cálcio com óleo de oliva) e, como grupo controle, dentes cujos canais foram preparados biomecanicamente mas não obturados. Trinta dias após o tratamento os animais foram mortos e as peças processados para análise histológica. Os resultados permitiram ordenar estatisticamente os materiais do melhor para o pior da seguinte maneira: a- Pasta de Maisto, b- Sealer 26 com iodofórmio, c- grupo controle, d- Pasta L&C. Foi observado diferença significante (p=0,01) somente quando os resultados dos diferentes grupos foram comparados com o grupo da pasta L&C. Foi também observado que a pasta L&C não foi biologicamente compatível enquanto os outros materiais foram biocompatíveis, porém suas velocidades de reabsorção não foram a mesma observada com as raízes dos dentes decíduos.
Análise histológica dos tecidos periapicais de dentes decíduos de cães após obturação de canais com diferentes materiais
Keywords: Dog's deciduous tooth; Root canal filling materials; Root canal therapy; Dentes decíduos de cães; Materiais obturadores do canal radicular; Tratamento de canal